Orchids of Suspa-Kshamawoti, Dolakha -An annotated checklist - Karki, S.; Ghimire, S. K. (Banko Janakari, 2019)
Suspa-Kshamawoti area of Dolakha district covers diverse vegetation types and harbors many interesting species of orchids. This paper documents 69 species of orchids covering 33 genera based on repeated field surveys and herbarium collections. Of them, 50 species are epiphytic (including lithophytes) and 19 species are terrestrial. Information regarding habit and habitat, phenology, host species and elevational range of distribution of each species are provided in the checklist